Distance leadership in international corporations : why organizations struggle when distances grow - Poser, Nadine (Springer Gabler, 2017)
Nadine Poser highlights the need for digital transformation in international organizations, not only from a business perspective but from a human point of view. Information technology is on the rise and with it the demand for highly influential digital leaders. The book covers the question under which conditions leadership can overcome physical distance. The author deliberately shifts the attention from those who lead to those who follow. Contents Literature Review: Leadership Theories - From Early Stages to Modern Concepts; Distance Leadership Hypotheses: Direct Effects of Leadership Behavior on Follower Self-Leadership and Performance; Moderation and Mediation Effects of Distance on the Leader-Follower Relationship Discussion: Leadership Behavior; Self-Leadership; Relationship Quality; Direct Effects and Mediation Effects of Distance Target Groups Academics and students in disciplines of leadership, organizational behavior, applied psychology Practitioners interested in digital leadership and leaders of virtual teams The Author Nadine Poser is a senior consultant with a focus on executive leadership and change at an international strategy consulting firm in Stuttgart. Educated in the Middle East and Liechtenstein, her academic and teaching expertise includes virtual leadership, lean leadership, and action learning. Series Editors The series Advances in Information Systems and Business Engineering is edited by Prof. Dr. Ulrike Baumöl, Prof. Dr. Jan vom Brocke, and Prof. Dr. Reinhard Jung.
Keywords: International business enterprises -- Management.; Leadership.; elektronické knihy; electronic books